Plant Community Analysis at Thakurwadi Village, Badlapur, Maharashtra, India: Assessment of Plant Community in Thakurwadi Village, Maharashtra, India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A Phytosociological study on the vegetation community was carried out at Thakurwadi village of Badlapur area, Maharashtra, India during 2018-2019. The main objectives of this study were to measure the frequency percentage, density, abundance, relative frequency, relative density, relative dominance and importance value index cohabiting in this locality. A total of 10 quadrats measuring 1.0m2 were laid randomly. The results showed that there are eight genera and six families. The most common species in this study area is Alternanthera triandra belonging to family Amaranthaceae.